Dobór perspektyw w zrównoważonej karcie wyników dla miast na prawach powiatu - Nieplowicz, Maria (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The article shows the proposal of widen the original Balanced Scorecard by adding additional perspectives taking into consideration polish cities specificity. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 267-273